Beyond Traditional Boundaries: Embracing Digital Transformation for Enhanced Management Efficiency at Micro and Small Business Enterprisess - Retnawati Siregar; Eko Sudarmanto (West Science Interdisciplinary Studies, 2023)
This research study explores the role of digital transformation in improving management efficiency in micro and small enterprises (MSEs) in West Java. The objectives of this study were to understand the adoption of digital technology among MSEs, assess its impact on management efficiency, and identify perceived benefits and challenges related to digital transformation. Data was collected through interviews and surveys with MSE owners and managers. Findings indicate significant adoption of digital technologies among MSEs, resulting in improved supply chain management, inventory control, decision-making, and customer relationship management. Perceived benefits include increased productivity, cost savings, improved customer satisfaction, and enhanced competitiveness. However, challenges such as limited resources, lack of digital skills, and resistance to change have been identified. These findings highlight the importance of embracing digital transformation to improve management efficiency in MSEs, while recognizing the need for targeted support and resources to address related challenges.